Single‐Center Evaluation of the Pharmacokinetics and Safety of the Angiotensin II Receptor Antagonist Azilsartan Medoxomil in Mild to Moderate Hepatic Impairment. (27th July 2017) - Dudkowski, Caroline; Karim, Aziz; Zhao, Zhen; Alonso, Alberto B.; Garg, Dyal; Preston, Richard A.
Abstract: Azilsartan medoxomil (AZL‐M) is a potent angiotensin II receptor blocker that decreases blood pressure in a dose‐dependent manner. It is a prodrug that is not detected in blood after its oral administration because of its rapid hydrolysis to the active moiety, azilsartan (AZL). AZL undergoes further metabolism to the major metabolite, M‐II, and minor metabolites. The objective of this study was to determine the effect of mild to moderate hepatic impairment on the pharmacokinetics of AZL and its major metabolite. This was a single‐center, open‐label, phase 1 parallel‐group study that examined the single‐dose (day 1) and multiple‐dose (days 4–8) — 40 mg — pharmacokinetics of AZL and M‐II in 16 subjects with mild and moderate hepatic impairment by Child‐Pugh classification (n = 8 per group) and subjects (n = 16) matched based on age, sex, race, weight, and smoking status. Mild or moderate hepatic impairment did not cause clinically meaningful increases in exposure to AZL and M‐II. Mild or moderate hepatic impairment had no clinically meaningful effect on the plasma protein binding of AZL and M‐II. Single and multiple doses of AZL‐M 40 mg were well tolerated in all subject groups. Based on the pharmacokinetic and tolerability findings, no dose adjustment of AZL‐M is required for subjects with mild and moderate hepatic impairment.